Diseño de un sistema de gestión académica de la Unidad Educativa “Diez de Agosto” del cantón Montalvo - Garcia Fernández, Edgar Ronaldo (2020)
Currently, every institution requires agility in all the processes it carries out, which is why this study took place in an educational unit in the Montalvo canton, where greater speed is required when registering enrollments and academic grades belonging to students of said institution, the proposal established for the educational establishment is to facilitate and expedite work within the secretariat department, the most appropriate way to do it successfully is through an academic management system of its own within the educational unit, but not software can be developed without having subsequently carried out a study focusing on its design, therefore, the starting point for obtaining a correct and quality software design is, through the analysis of both functional and non-functional requirements therefore, the research methodology used was qualitative; interview technique using an open-ended questionnaire; The detail of the processes necessary for the development of the system was made through the implementation of UML diagrams such as: use cases, activities, sequence, classes and entity-relationship; these being the necessary tools for the person in charge of programming or developing the system.